Managerial economics for beginners - Normala Ismail; Mohamad Kamil Ariff Khalid (Penerbit Universiti Malaya, 2015)
This book is written for both undergraduate and post graduate students to give them an insight and better understanding of the tools of business and managerial economics. This book is arranged into 7 chapters and comes with schedules, diagrams, and examples of calculations. Sample questions and answers are also provided at the end of each chapter for students to assess themselves. Chapter One examines the nature and scope of managerial economics. Chapter Two reviews the optimisation technique showing how a firm seeks to achieve its aims and objectives most efficiently subject to contraints. Chapters Three and Four analyze the demand theory, the empirical estimation of demand and demand forecasting. Chapters Five and Six presents the theory and measurement of the firm's production and costs. A complete presentation and discussion of input substitution in production and short and long run cost curves is also covered in Chapter Six. Finally, Chapter Seven analyses how price and output are determined under various forms of market organisation.